Efektifitas Media Hema-Magz dalam Meningkatkan Pengetahuan PHBS di Lingkungan Kampus - Satya, Malinda Capri Nurul; Iwan Abdi Suandana; Yoswenita Susindra; Lisus Setyowati; Dian Kartika Sari (Puslitbang Sinergis Asa Professional, 2025)
The implementation of Clean and Healthy Living Behaviors (PHBS) is essential for establishing positive habits across a university campus. However, PHBS within the campus environment is often neglected. A significant portion of the academic community has not yet fully adopted these behaviors, as evidenced by practices such as smoking on campus, consuming unhealthy food and beverages, and indiscriminate spitting. This situation is likely due to various factors, including a lack of knowledge about PHBS, insufficient outreach, and inadequate facilities. Poor adherence to PHBS can lead to infectious diseases like eye infections, diarrhea, anemia, and helminthiasis. One effective method to enhance the knowledge and awareness of PHBS among the academic community is through various information media, such as online magazines or e-magazines. Hema-Magz (Healthy Motion Magazine) is an e-magazine development containing information about PHBS on campus. This study aimed to evaluate the effectiveness of the Hema-Magz media on respondents' knowledge before and after the intervention. This research employed a quantitative design with a pretest-posttest approach, involving 15 respondents from the Tefa House of Health Promotion academic community. The research instrument consisted of 10 questions related to PHBS. The collected data were analyzed using a paired sample t-test. The results indicated an increase in the average knowledge score from 76.6% to 88.4%. Furthermore, the paired sample t-test yielded a p-value of 0.024, signifying a statistically significant difference in knowledge before and after using Hema-Magz. This media is effective in improving knowledge by offering engaging and interactive content. Further development into a mobile application is recommended to achieve a broader reach.